Effect on the mechanical properties of sheet metals after the use of drawbeads in deep drawing - Schmid, Harald; Merklein, Marion (5th International Conference on New Forming Technology ICNFT Bremen 2018, 2018)
The use of modern and more complex materials leads to a need for detailed knowledge and controlling of the material flow. Next to the blank holder force or the lubrication system, drawbeads are nowadays one common way to bring serial forming processes under control. Although drawbeads are already well investigated regarding their retention forces, the effect on the resulting mechanical properties after a drawbead passage is not analysed in detail yet. This work will show the influence of a common drawbead geometry used in forming processes on typical mechanical properties of sheet metal. Therefore, two different sheet metal materials are preloaded in a modified strip drawing test with industrial used drawbead geometry. In testing, three different pressure levels between 2.5 MPa and 7.5 MPa and three levels of drawing speed between 10 mm/s and 50 mm/s are combined to nine variations which will be examined. Afterwards, specimens are cut out by a laser cutting machine of the drawn strips. Those already preloaded and deformed specimens are then tested under standard conditions with the use of an optical measurement system. The results like tensile strength or elongation at fracture are compared to the initial state and each other and discussed with consideration of pressure and speed levels to work out the main effects. Those results are a contribution for the optimization of deep drawing simulations of parts including drawbeads or to evaluate the influence of drawbeads on forming processes to specify or even expand process limitations.
LFT Import::2019-08-05 (2317)
Keywords: Deep drawing; Hardening; Sheet metal